SPIRITUALITAS DALAM KONTEKS KONSELING - Aam Imaduddin (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2017)
Spirituality in the context of counseling have the same potential both positive or negative, counselors need to have a standardized competencies to integrating spiritual and religious dimension in the counseling process. Spirituality is a part of the individual's development that characterizes humanity and as an indicator of mental health. Standarized competencies in integrating spiritual dan religious in counseling process can be achieved with education.